ULTRASONOGRAPHY OF SUBCUTANEOUS FAT AS A METHOD OF INSULIN INDUCED LIPOHYPERTROPHY DIAGNOSTICS IN DIABETIC PATIENTS - N. I. Volkova; I. U. Davidenko (Медицинский вестник Юга России, 2013)
Purpose: To evaluate the frequency of insulin induced lipohypertrophy (LH) in diabetic patients revealed by observation and palpation techniques, as well as ultrasonography of subcutaneous fat.Materials and methods: This study was done on 192 diabetic patients (mean duration of disease was 10 years) who had been under the treatment with insulin a mean 8 years. Observation and palpation techniques, as well as ultrasonography of subcutaneous fat were used in assessing LH in these diabetics.Results: On the basis of palpation LH were revealed in 27,7% patients. Further ultrasonography of injection sites was performed to all patients. LH were revealed in 83,2% patients, including those subjects with palpatory changes. Pathologic areas of subcutaneous fat the most often were occurred in paraumbilical regions – 61% patients.Summary: Problem of LH has been modified. As a result, traditional methods of LH diagnostics have become not an informative. This question is needed an additional investigation.